(untitled) (Bangladesh Medical Journal Khulna, 2012)
Chronic obstructive pulmonary diseases have increased in prevalence and the rate of death of this chronic inflammatory disease of the airways has also risen despite recent advances in medical treatments. The dental health care professionals must be prepared to treat more medically compromised individuals. Because dental professionals operate at the origin of the upper airway and many dental procedures are deemed stressful, patients with chronic respiratory diseases are at special risk. This article will review the patho-physiology and discuss the recognition and management of dental patients with these diseases and provide an understanding on how to avoid precipitating factors that could initiate an acute episode in the dental care setting. The most important factor in preventing COPD is helping patients stop smoking. DOI: http://dx.doi.org/10.3329/bmjk.v44i1-2.10472 Bang Med J (Khulna) 2011: 44(1&2) 21-24